Facile Fabrication of Nanoparticles Stacked 2, 6‐diamino‐3, 5‐dinitropyrazine‐1‐oxide (LLM‐105) Sub‐microspheres via Electrospray Deposition. Issue 2 (14th November 2017) - Huang, Chuan; Liu, Jiahui; Ding, Ling; Wang, Dunju; Yang, Zhijian; Nie, Fude
Abstract: In this study, nanoparticles stacked 2, 6‐diamino‐3, 5‐dinitropyrazine‐1‐oxide (LLM‐105) sub‐microspheres were successfully fabricated by electrospray deposition. These monodisperse sub‐microspheres with a diameter from 200–500 nm are composed of 50 nm nanoparticles, and after preserved six months these spheres retain the same structure and morphology. The effect of process parameter including flow rate and nozzle size on the size and morphology of sub‐microsphere is investigated. The results show that, for a given solution concentration the nozzle size has little effect while the flow rate shows a significant effect. The X‐ray diffraction (XRD) and Fourier transform infrared spectroscopy (FT‐IR) results exhibit that the as‐prepared sub‐microspheres have the same crystal and chemical structure as the raw materials. The thermal behavior performed by simultaneous thermal analysis (TG‐DSC) verifies that in comparison to the raw materials sub‐microspheres have a lower onset degradation temperature. Abstract :